Qualidade de sementes e rizogênese in vitro em Peltophorum dubium (Sprengel) Taubert - Gomes, Clarissa Stahl (2017)
Peltophorum dubium (Sprengel) Taubert is a native species occurring from the Northeast region to the Southern region of the Brazil. Its rusticity and rapid growth in addition to the durability of its wood give it great environmental and economic importance. Their seeds have dormancy and are classified as orthodox, conferring specific physical, sanitary and physiological characteristics. In our Research Group several studies have already been developed with this species, however, some components of the in vitro rooting medium have not yet been evaluated. Thus, the objective of the present study was to optimize the micropropagation process of Peltophorum dubium, in particular the in vitro rhizogenesis stage of the shoots. The quality of the seeds that gave explants to in vitro rhizogenesis experiments was analyzed for moisture, weight of one thousand seeds, biometry, sanity and germination. In the in vitro rhizogenesis, nutritive medium components such as pH, agar and sucrose were evaluated at different levels and concentrations, combined with the presence or absence of vermiculite. In addition, different nutritive medium, in the absence of sucrose, were analyzed, associated to two growing periods. The degree of moisture and the weight of one thousand seeds confirmed its classification as orthodox and small seeds. The dimensions evaluated, as well as the small amplitude of variation, confirmed the homogeneity of the lot. The seeds have associated to 10 fungi genera and presented 86% germination. In the absence of sucrose, higher averages of root formation and length were observed (57.14 % and 2.79 cm respectively). Regardless of the concentration of agar, the presence of vermiculite favored the formation of roots (17.46 versus 3.2%) and regardless of sucrose concentrations, vermiculite impaired the quality of the root system (0.46 versus 2.41 cm and 9.51 versus 1.59% for length and secondary roots respectively). The results observed for calogenesis indicated that the presence of vermiculite in the culture medium is controversial, varying according to the composition of the nutritive medium, with respect to agar and sucrose. After 60 days of in vitro culture the highest mean (59.83%) of rhizogenesis was observed for the species. The physical characteristics of the seed lot are within the standard registered in the literature. The pH levels and agar concentrations do not influence in vitro rhizogenesis. The absence of sucrose promotes greater root formation, in addition to greater length. The presence of vermiculite increases the rooting, however it negatively affects the quality of the root system. Addition of the substrate affects the callogenesis, varying according to the composition of the nutritive medium used. The nutritive medium does not influence the in vitro rhizogenesis, but the period of growt is relevant, presenting at 60 days a greater formation and length of roots as well as of secondary roots.